LOGISTICS MODELLING OF ELECTROMOBILITY-BASED PARCEL DISTRIBUTION IN URBAN ENVIRONMENT - Juhász, János (Journal of Applied Engineering Science, 2025)
Various industries increasingly adopt sustainable and eco-friendly technologies to distribute finished goods in today's globalized world. In Miskolc, electromobility and logistics play a crucial role in ensuring the efficient supply of these products. This study introduces a novel optimization model for sustainable urban parcel delivery that integrates electromobility and green logistics. The model applies a genetic algorithm to optimize resource allocation and delivery routes, offering control over electric vehicle usage and responsiveness to varying customer demands and cost constraints for the infrastructural characteristics of a disadvantaged Miskolc region. Using this method, the research demonstrates improved sustainability, cost-effectiveness, and flexibility in urban logistics—particularly in response to the challenges posed by the rise of e-commerce. The findings contribute to the advancement of eco-friendly and efficient distribution systems.
Keywords: supply chain, logistics, electromobility, parcel distribution, general modelling